Efficacy of milnacipran in outpatients experiencing major depression non respondent to SSRIs: a 12-week open study (Archives of Clinical Psychiatry, 2010)
BACKGROUND: The objective of this study is to evaluate the efficacy of milnacipran in outpatients experiencing severe MDD non-respondent to adequate time and dosing of SSRI therapy. METHODS: A 12 week multi-centric study open study was designed to evaluate the efficacy of milnacipran after a SRRI trial failure. Complete remission (HAMD-17 < 8) was the principal outcome. Secondary outcomes were response (HAM > 50%), CGI and quality of life measure (WHOQOL-Bref). RESULTS: The mean HAMD-17 score of the sample was 27 (7.2). The remission rates for minalcipran were 17.5% and response 61.3%. At baseline, 70.9% of the patients were markedly or severely ill. At treatment end, 48.1% of the patients were normal asymptomatic or borderline and 20.2% were mildly ill. Also, the four domains of WHOQOL-Bref, a generic instrument of Quality of Life, presented statistical and clinical differences. DISCUSSION: Our findings suggest that milnacipran is a possible option to be used in patients that were non-respondents to SSRIs. Since there is no evidence in literature that one single antidepressant is the best second step when an SSRI fail, milnacipran should be considered in the case of severe depressed patients.